Extensive Direct Subcortical Cerebellum-Basal Ganglia Connections in Human Brain as Revealed by Constrained Spherical Deconvolution Tractography - Demetrio eMilardi; Demetrio eMilardi; Alessandro eArrigo; Giuseppe Pio Anastasi; Alberto eCacciola; Silvia eMarino; Enricomaria eMormina; Alessandro eCalamuneri; Daniele eBruschetta; Giuseppina eCutroneo; Fabio eTrimarchi; Angelo eQuartarone; et al. (Frontiers Media S.A., 2016)
The connections between the cerebellum and basal ganglia were assumed to occur at the level of neocortex. However evidences from animal data have challenged this old perspective showing extensive subcortical pathways linking the cerebellum with the basal ganglia. Here we tested the hypothesis if these connections also exist between the cerebellum and basal ganglia in the human brain by using diffusion magnetic resonance imaging and tractography. Fifteen healthy subjects were analyzed by using constrained spherical deconvolution technique obtained with a 3T magnetic resonance imaging scanner. We found extensive connections running between the subthalamic nucleus and cerebellar cortex and, as novel result, we demonstrated a direct route linking the dentate nucleus to the internal globus pallidus as well as to the substantia nigra. These findings may open a new scenario on the interpretation of basal ganglia disorders.